ANALISIS BUKU TEMATIK SISWA MUATAN IPA DITINJAU DARI UNSUR STEAM (Studi Deskriptif Pada Tema 6 Kelas VI SD) - Wiwi Susanti; Endang Widi Winarni; Dwi Anggraini (Universitas Bengkulu, 2022)
The objective of this research was to know the subject matter of Science, Technology, Engineering, Art, and Mathematics (STEAM) in the Thematic book for student science Six class at Elementary School. This research of descriptive qualitative to analyze in the book Thematic for student science Six class at Elementary School. The data collected used analysis of the elements of STEAM in the Thematic book of science student content use the Analyze sheet of the Guidelines for the Elements of STEAM. The results of the research showed that the difference of elements of STEAM in the Thematic book of science. The Highest element from 4 elements are Science with the percentage of (33%), technology elements with the percentage of (9%), engineering elements with the percentage of (7%), Art elements) with the percentage of (22%), and mathematics elements with the percentage of (9%). The percentage of this research found the technology element is the smallest compared to the percentage of the other four elements. Based on the result above, it can be concluded that the elements of STEAM technology, engineering, and mathematics in the serve Thematic book in the science subject are still lowest for student Six class at Elementary School.